Specters of Germany colonial rivalry & scholarship in the Philippine reform movement & revolution - Weston, Nathaniel Parker (Nathaniel Parker Weston Ateneo de Manila University Press, 2021)
This book examines the origins of Philippine scholarship in the context of imperialist rivalry between Germany and Spain. It investigates the ways that Filipino writers played on these tensions in the ongoing struggle for colonial reform in the late nineteenth century. Filipino scholarship and other writing coupled with the real and perceived threat of Germany continued to circulate after the outbreak of the 1896 Philippine Revolution and Philippine-American War that followed. Specters of Germany analyzes works on the Philippines by prominent German-speaking, Spanish, and US writers, as well as those by Gregorio Sancianco, Graciano López Jaena, Pedro Paterno, José Rizal, Isabelo de los Reyes, Mariano Ponce, and other Filipino authors. Ultimately, it demonstrates that Philippine colonial studies served as a potent weapon in the fight for national self-determination and the politics of imperialism that surrounded it. --Back cover.